Design and simulation of Na2Nb4O11 dielectric resonator antenna added with Bi2O3 for microwave applications. Issue 5 (21st March 2016) - Oliveira, R.G.M.; Freitas, D.B.; Romeu, M.C.; Silva, M.A.S.; Sales, A. J. M.; Ferreira, A.C.; Filho, J.M.S.; Sombra, A.S.B.
ABSTRACT: In this paper is reported an experimental and numerical investigation of the microwave dielectric properties of Na2 Nb4 O11 (NN), ceramic matrix added with (0, 2, 5, and 10 wt%) of Bi2 O3, obtained through a new procedure based on the solid‐state method. The experimental and theoretical characteristics of the resonator like return loss, bandwidth, input impedance are in good agreement. The simulations of radiation patterns are presented. For NN reference sample, frequency response bandwidth is of 43MHz (simulated) and 35MHz (experimental) for frequency operation around 2.28 GHz. The NN reference sample showed a dielectric permittivity around 58.4, with loss around 7.3 × 10 − 3 . The adding of bismuth oxide (2 and 5 wt%) reduced the value of the dielectric permittivity, otherwise the adding of 10 wt% increases its value. The temperature coefficient of resonant frequency (τf) was also measured for all dielectric samples. The values obtained were in the range of −3378 to −250ppm/°C. The results obtained confirm the necessity of producing composites of this material with others positive τf materials for obtaining dielectric resonator antennas with τf  = 0. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1211–1217, 2016